If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 3b = b Combine like terms: 8b + 3b = 11b 11b = b Solving 11b = b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 11b + -1b = b + -1b Combine like terms: 11b + -1b = 10b 10b = b + -1b Combine like terms: b + -1b = 0 10b = 0 Divide each side by '10'. b = 0.0 Simplifying b = 0.0
| 2x^4-9x^3-4x^2=0 | | 8x+9.84=4x+14 | | 2w+8w+w=329 | | 5x-3x+5=x+8 | | x^2+2x-33=0 | | 11h-5h+16=4 | | 6.9m+1.96=-49.79 | | 0.2x+0.4=3.6 | | 7.7x=-60.06 | | x-4=7.26 | | 10-6x-4+8x=12 | | 0=35-5x-2x | | -5y=4.95 | | p(4b-1)=2(9b+3) | | x+3.1=7.3 | | 14s^2-167st-12t^2=0 | | x^2+5x+31= | | 0=7m+4-3m | | x+10=-30 | | (x+5)(3x-9)=0 | | s=2*3.14*r^2+2*3.14*r*h | | 2(2t-3)=6(t-2) | | 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x | | 7t-8=2+5t | | -2+p+2p+2=-12 | | 5m-12=-10+4m | | -36-b-4b=64 | | 5m+1=-23 | | 11.3-7.2=-3.82 | | 1.3-7.2=-3.82 | | 8.4s-s=14.8 | | -5z+3z-7=8z-1-6 |